The Organizational Culture Strategy SMEs During Economic Crises - Nguyen Ngoc Khanh Dung; Dang Anh Tuan (Emerging Science Journal, 2023)
The importance of organizational culture in the operation and performance of businesses has been widely acknowledged, but there is inconsistency in findings about the impact of culture on organizational performance across studies. This study aimed to achieve two objectives: first, to establish the relationship between the quality of accounting information systems (AIS), organizational culture, and the financial performance of small and medium enterprises (SMEs) in Vietnam; and second, to survey the organizational culture strategy of Vietnamese SMEs in the context of economic crises. The study survey was conducted in May 2023 and involved 242 SMEs in Vietnam. The research model was tested using Smart PLS. The results suggest that AIS has a positive relationship with both organizational culture and the financial performance of SMEs. However, organizational culture only affects financial performance related to organizational adaptability during a crisis. Moreover, a flexible, external adaptation, and balanced cultural approach strategy has a significant impact on the financial performance of SMEs. During a crisis, managers expect employees to adapt in order to achieve strategic goals and plans while simultaneously balancing stability, engagement, and employee satisfaction to achieve organizational effectiveness. Doi: 10.28991/ESJ-2023-07-06-015 Full Text: PDF